Tingkat Pemanfaatan Sumberdaya Perikanan Pelagis Besar dan Kesejahteraan Rumah Tangga Nelayan di Perairan Kota Jayapura, Provinsi Papua - Sasarari, Rosmina Rose; Fahrudin, Achmad; Zulbainarni, Nimmi (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2019)
The territorial waters of Jayapura City, especially the waters of North Jayapura and South Jayapura are the centers of capture fisheries activities of big pelagic species, namely tuna and skipjack tuna, which need to be utilized to provide welfare for the community, especially fishermen in a sustainable manner. For this reason, this study was conducted to analyze the level of utilization of big pelagic fisheries resources and analyze the welfare level of big pelagic fishermen households in Jayapura city waters. Primary data collection is done through interviews with respondents who are randomly selected. Utilization level analysis was carried out using multispecies bioeconomic analysis and analysis of fisherman welfare levels was carried out using the criteria of the poverty line set by the Central Bureau of Statistics. The results showed the actual utilization rates of tuna and skipjack fisheries resources in the waters of Jayapura City are still in the continuous production of MSY and MEY. Nevertheless, the utilization of these big pelagic fisheries resources needs to be supported by economic institutions that can better distribute their benefits, especially to fishermen. This is because based on the survey conducted; most of the household welfare of the big pelagic fishermen tuna and cakalang in the waters of Jayapura City are still classified as not prosperous.